2013
DOI: 10.1186/1471-2334-13-224
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of quadrivalent versus trivalent inactivated influenza vaccine: a randomized, controlled trial in adults

Abstract: BackgroundTwo phylogenetic lineages of influenza B virus coexist and circulate in the human population (B/Yamagata and B/Victoria) but only one B-strain is included in each seasonal vaccine. Mismatch regularly occurs between the recommended and circulating B-strain. Inclusion of both lineages in vaccines may offer better protection against influenza.MethodsThis study (NCT00714285) assessed the immunogenicity and safety of two candidate quadrivalent influenza vaccines (QIV) containing two A- and two B-strains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 40 publications
1
30
1
2
Order By: Relevance
“…Among adults the most common safety complaints were injection-site pain and systemic reactions, such as myalgia, headaches, and fatigue (123,125,127,129,130,309). The first postlicensure safety assessment of VAERS reports covering the 2013-14 and 2014-15 seasons noted a safety profile similar to that of IIV3.…”
Section: Adultsmentioning
confidence: 99%
“…Among adults the most common safety complaints were injection-site pain and systemic reactions, such as myalgia, headaches, and fatigue (123,125,127,129,130,309). The first postlicensure safety assessment of VAERS reports covering the 2013-14 and 2014-15 seasons noted a safety profile similar to that of IIV3.…”
Section: Adultsmentioning
confidence: 99%
“…There were no differences between the trivalent and quadrivalent preparations with regard to safety and reactogenicity. [36][37][38][39][40][41] There is an increased cost associated with the use of quadrivalent vaccines but modeling studies suggest a significant societal cost saving even if the cost is significantly higher than the trivalent preparation. [42][43][44] …”
Section: Trivalent/ Quadrivalent Influenza Vaccinesmentioning
confidence: 99%
“…All studies were funded by the manufacturer (GSK). A summary on the findings is shown in [20]. One hundred and four participants were included in each group and the results showed that predefined non-inferiority criteria were reached for both QIVs compared to the TIVs for the three strains in the TIV.…”
Section: Immunogenicity Of the Vaccinementioning
confidence: 99%